Does marriage make people happy, or do happy people get married? - Alois Stutzer; Bruno S. Frey (Institute for the Study of Labor (IZA), 2005)
This paper analyzes the causal relationships between marriage and subjective well-being in a longitudinal data set spanning 17 years. We find evidence that happier singles opt more likely for marriage and that there are large differences in the benefits from marriage between couples. Potential, as well as actual, division of labor seems to contribute to spouses' wellbeing, especially for women and when there is a young family to raise. In contrast, large differences in the partners' educational level have a negative effect on experienced life satisfaction.
Keywords: D13; I31; J12; 330; division of labor; marriage; selection; subjective well-being; Kausalanalyse; Deutschland; Ehe; Lebenszufriedenheit